Circular economy opportunities for inorganic waste management: An applied analysis based on recycling center data - Agni Lili Ariyanti; Aisyah Fakhirah; Akbar Putra Alfareza; Arif Nur Surdianto; Feivie Wihdya Solikhah; Yulia Azizah Suleman; Gangsar Edi Laksono; Purwono (Applied Environmental Science, 2026)
Background: Waste is no longer regarded solely as refuse but also as a potential resource in the circular economy, particularly through recycling center (hereinafter referred to as pusat daur ulang-PDU) mechanisms. This study aims to analyze the circular economic potential of inorganic solid waste based on actual selling price data from PDUs in Purbalingga, Central Java, Indonesia. Previous studies have highlighted the importance of waste separation and local PDUs in promoting community-based waste management, yet few have quantified the circular economic value of specific inorganic waste types. Methods: This research employs a descriptive quantitative approach using secondary data collected from government institutions and local PDUs. Analytical methods include compositional waste analysis and basic statistical comparisons (T-Test) across years and waste types (polyethylene terephthalate-PET, scrap papers, and cans). Findings: PET accounted for an average of 18.53% of total waste between 2021 and 2024, far higher than paper (8.96%) and cans (0.66%). Statistical analysis confirmed significant differences between PET and the other two types (p < 0.05, Cohen’s d > 3). Scenario modeling showed that if 14.8% of the population participated by contributing 3 kg of PET per household, approximately 460 tons/day could be recovered, generating meaningful household income and reducing landfill burden. Conclusion: The study concludes that supporting PDUs and encouraging less than 20% household participation in PET separation could substantially reduce waste volumes while strengthening household income streams. Novelty/Originality of this article: The integration of compositional waste data and local price structures provides a data-driven valuation of inorganic household waste, offering practical guidance for policy and local planning in sustainable circular economy strategies.